2017
DOI: 10.1590/1516-4446-2016-2139
|View full text |Cite
|
Sign up to set email alerts
|

Screening for common mental disorders using the SRQ-20 in Brazil: what are the alternative strategies for analysis?

Abstract: Objective: To analyze the prevalence of common mental disorders (CMD) assessed with the Self Reporting Questionnaire (SRQ-20), using the established cutoff point, and comparing it with the results of a joint correspondence factor analysis (CFA) and cluster analysis and of a latent class analysis (LCA). Methods: A cross-sectional study was carried out in an urban sample of 1,095 women aged 19 to 55 years. Joint CFA-cluster analysis and LCA were used. Results: We found a high prevalence of CMD, regardless of cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
11

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 23 publications
1
28
0
11
Order By: Relevance
“…Furthermore; majority of scales previously used for the assessment of mental health status at clinical and community settings performing varying degree of validity across settings, populations and cultures. These scales are the Beck Depression Inventory (BDI-II) scale, the structured clinical interview for depression in DSM-5, comprehensive psychopathological rating scale, and the SRQ-20 were few among many [27, 4143]. Despite it has many limitations; the SRQ-20 demonstrated better validity in culture of developing nations including Ethiopia [26].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore; majority of scales previously used for the assessment of mental health status at clinical and community settings performing varying degree of validity across settings, populations and cultures. These scales are the Beck Depression Inventory (BDI-II) scale, the structured clinical interview for depression in DSM-5, comprehensive psychopathological rating scale, and the SRQ-20 were few among many [27, 4143]. Despite it has many limitations; the SRQ-20 demonstrated better validity in culture of developing nations including Ethiopia [26].…”
Section: Discussionmentioning
confidence: 99%
“…However; since the SRQ-20 is not a diagnostic tool; the use of cut off point doesn’t matter as it is enough to establish the mental health profile of a given population at a given time. Furthermore; study have showed that the cut off point SRQ-20 tends to underestimate prevalence of mental disorders among women [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The questionnaire was translated into local languages Afan Oromo and Amharic and validated to Ethiopian context. As common mental disorders (CMDs) refers to the set of signs and symptoms of non-psychotic depression, anxiety, and somatoform disorders, considering how challenging it can be to diagnose these disorders in primary care practice, the World Health Organization (WHO) developed the Self Reporting Questionnaire (SRQ-20), a screening instrument to identify suspected CMDs cases in primary care settings [21]. The SRQ-20 has 20 yes/no questions and it has been validated in Ethiopia, with high sensitivity (85.7%) and specificity (75.6%) [22].…”
Section: Methodsmentioning
confidence: 99%
“…These include symptoms of depressive-anxious mood, psychosomatic complaints, decreased vital energy, and depressed thoughts. 15,16 Although highly prevalent globally, CMD is quite often overlooked and may not be identified as psychiatric morbidity in up to two-thirds of cases by health professionals in primary care. 16,17 Other psychosocial factors, such as maternal stress and social support (SS), seem to be associated with asthma morbidity in the child.…”
Section: Introductionmentioning
confidence: 99%